The Pregnancy Vaccine Effectiveness Network (PREVENT): Establishing a Multi-Country Cohort to Estimate Vaccine Effectiveness (VE) against Hospitalized Influenza During Pregnancy. (4th October 2017) - Ball, Sarah; Naleway, Allison; Kwong, Jeffrey C; Reagan, Annette K; Simmonds, Kimberley; Feldman, Becca; Azziz-Baumgartner, Eduardo; Wyant, Brandy; Klein, Nicola P; Fell, Deshayne; Effler, Paul; Booth, Stephanie; et al.
Abstract: Background: Pregnant women are at greater risk of complications from influenza (flu) infection than the general population. Although vaccination is an effective method to prevent influenza, the vaccine is underutilized during pregnancy. A challenge to maternal flu vaccination is the paucity of data about the effectiveness of inactivated influenza vaccines (IIV) in preventing severe outcomes in pregnant women. To inform policy and address this knowledge gap, CDC developed a multi-country collaboration to investigate the preventive value of IIV during pregnancy during multiple flu seasons. We present the progress to date of this Network. Methods: PREVENT was established in April 2016 to: i) estimate incidence of influenza and vaccination rates; ii) describe epidemiologic characteristics associated with illness; and iii) estimate IIV effectiveness in preventing hospitalizations during pregnancy associated with RT PCR -confirmed influenza. We selected sites that could identify the population of women known to be pregnant during flu seasons and integrate their hospitalization data, clinical laboratory testing, and vaccination records. We will assess VE using the case test-negative control design and use meta-analyses to pool VE estimates across sites and account for significant differences. Primary analyses will be completed by August 2017. Results: Seven sites in Australia, Canada, Israel, and the US were selected; a protocol and data dictionary were finalized. We identified 1, 024 pregnant women hospitalized with acute respiratory illness and RT-PCR tested, during six influenza seasons (2010–11 through 2015–16). Of the qualifying women, 550 (54%) tested positive for flu. Positivity varied by site (range 41% (US)–61.8% (Ontario, CAN)), and vaccination coverage varied across sites and seasons (range 7.3% (Ontario, CAN)–46% (US)). Analyses will examine flu season characteristics, vaccination patterns, and clinical and birth outcomes related to respiratory illness during pregnancy and flu incidence. Conclusion: Laboratory-confirmed influenza hospitalization during pregnancy is a relatively low-frequency event. Pooling data across multiple sites offers a way to estimate VE against severe influenza outcomes in pregnant women that is informative to influenza vaccine policy. Disclosures: A. Naleway, MedImmune: Investigator, Research grant; Pfizer: Investigator, Research grant; Merck: Investigator, Grant recipient; N. P. Klein, GSK: Investigator, Research grant; sanofi pasteur: Investigator, Grant recipient; Merck & Co: Investigator, Grant recipient; MedImmune: Investigator, Grant recipient; Protein Science: Investigator, Research grant; Pfizer: Investigator, Grant recipient; S. Irving, Medimmune/AstraZeneca: Investigator, Research support